Uso da automação para estimação de consumo alimentar, peso vivo e eficiência alimentar em bovinos de corte - Crozara, Adriano Santana (2018)
The objective of this study was to verify the correlation of residual feed intake and gain and body weight variables obtained by traditional weighing methods, every 14 days and fasting animals, and daily weighing using an automated scale, in food efficiency tests, also verify the feasibility of reducing the duration of the test using the automated system, identifying the amount of minimum and adequate days for accurate measurement of residual feed intake, weight gain, dry matter intake and ratio conversion. A total of 28 Nellore and 16 Guzera cattle were used, not castrated and aged between 18 and 21 months. The test had a duration of 70 days, with an initial weighing, four intermediate and final weighing. The animals were also weighed daily by means of electronic scales coupled to drinking fountains. The variables measured to generate the food efficiency information (RC, FE and RFI) were: dry matter intake (DMI, kg/day); average daily gain (ADG, kg / day); live weight (LW, kg); subcutaneous fat thickness (mm) and, later, residual feed intake (RFI, kg/day). Cattle effects went through analysis of variance of repeated measures, to verify the need to analyze it separately. Averages test was performed for initial and final weight characteristics, ADG, RC and FE for the two scales. For RFI, originating from traditional and automated weighing information, was made a correlation between them, to verifying their magnitude. Significance of the slopes of the weight regression curves from the two scales was verified. Correlations were made between the weights from the traditional and automated scale, considering the six weighings by the traditional balance during the efficiency test and automated weighing disregarding the days of possible interference in weight due to fasting (one day before and one after the fast). To verify the possible reduction of time for food efficiency tests, using the automated weighing system, the variables of RFI, BW, ADG and DMI were grouped, obtaining an average value every four days. These data are representative for days 14, 18, 22, 26, 30, 34, 38, 42, 46, 50, 54, 58, 62 and 66 and 70. Thus, from the sequential information of the four characteristics, the Pearson and Spearman correlation coefficients were generated in relation to the final information (70th day) for the same characteristics and their variations. The moment when the correlation was significant at 0.1% and difference between variances below 1% for each characteristic was considered as adequate for the conclusion time for respective characteristic in food efficiency test. No differences were found between means of the two scales for initial and final weights, RC and FE, only for ADG. The Pearson and Spearman correlations of the RFI between the values obtained by weighing using the traditional and automated scale were, respectively, 0.75 and 0.76. The slopes of the lines for weights between the two scales were statistically similar. To reduce the test time, considering the reduction of the variances and the correlation coefficients, it is recommended that for the characteristics of ADG and RC it is possible to reduce to 58 days, for DMI 38 days and for RFI 34 days. The use of automated scale can serve as an option for RFI information in food efficiency tests. By conducting them using these it is possible to reduce the test period according to the desired characteristic, average gain and ratio conversion 58 days, for dry matter intake 38 days and for residual feed intake 34 days, obtaining reliable results.